INFLUENCE OF COMPETENCE, INDEPENDENCE, SPIRITUAL QUOTIENT, EMOTIONAL QUOTIENT, AND AUDIT TENURE ON AUDIT QUALITY - Ready Wicaksono; Mispiyanti Mispiyanti (UNIB Press, 2021)
Audit quality is the probability of an assessment given by the auditor about the discovery of a violation in the client's accounting system and reports the violation. The purpose of this study is to obtain empirical evidence of competence, independence, spiritual quotient, emotional quotient, and audit tenure variables on audit quality. This research is quantitative. The population in this study is the Public Accountant Office in Yogyakarta with the sample selection method that is convenience sampling. The data is taken from respondents' responses to positive and negative statements contained in the questionnaire. Data processing and hypothesis testing techniques using SPSS version 22. The results of this study prove that competence, independence, spiritual quotient, emotional quotient, and audit tenure have a significant positive effect on audit quality. This shows that an auditor must have good personal quality, adequate knowledge, and special expertise in his field, not influenced by other parties, and is obliged to be honest not only to the management and owners of the company but also users of financial statements, have a spiritual and emotional good, and a deeper and more complete understanding of the company's operational activities, along with the increase in the number of years of the audit engagement with the company so that it has an impact on the quality of audits produced.